Differences in the Proteomic and Metabolomic Response of Quercus suber and Quercus variabilis During the Early Stages of Phytophthora cinnamomi Infection - Saiz-Fernández, Iñigo; Đorđević, Biljana; Kerchev, Pavel; Černý, Martin; Jung, Thomas; Berka, Miroslav; Fu, Chuen-Hsu; Horta Jung, Marília; Brzobohatý, Břetislav (Frontiers in Microbiology, 2022)
Phytophthora cinnamomi Rands is a cosmopolite and phyllophagous pathogen of woody plants which during the last couple of centuries has spread all over the world from its center of origin in Southeast Asia. Despite Chinese cork tree (Quercus variabilis Blume) forests native to Asia being generally healthy, the populations of cork trees (Quercus suber L.) in Europe have been decimated by P. cinnamomi. The present study tries to identify the differences in the early proteomic and metabolomic response of these two tree species that lead to their contrasting susceptibility to P. cinnamomi attack. By using micropropagated clonal plants, we tried to minimize the plant-to-plant differences in the defense response that is maximized by the high intraspecific genetic variability inherent to the Quercus genus. The evolution on the content of Phytophthora proteins in the roots during the first 36 hours after inoculation suggest a slower infection process in Q. variabilis plants. These plants displayed a significant decrease in sugars in the roots, together with a downregulation of proteins related to carbon metabolism. In the leaves, the biggest changes in proteomic profiling were observed 16 hours after inoculation. and included increased abundance of peroxidases, superoxidedismutases and gluthatione S-transferases in Q. variabilis plants, which probably aided its resistance against P. cinnamomi attack.